The effect of the corporate governance of Philippine GOCCs on the issued annual audit opinion - dela Pasion, Shannen Mari C. (Animo Repository, 2023)
Government-owned or Controlled Corporations (GOCCs) are expected to function as both economic drivers and service providers to the general public. Due to present economic conditions that pose risks to GOCCs’ audit outcomes, the demand for transparency and accountability in corporate governance and audit opinion among these is heightened. The researchers aim to determine the effect of the corporate governance of GOCCs on their annual audit opinion. Ordered logit model and logistic regression were utilized in this quantitative causal study. It follows the audit opinion as the ordinal dependent variable and the corporate governance, as measured by the finance component of the performance scorecard, as the independent variable. The performance scorecards and audit opinions for the years 2015 to 2019 were retrieved from each GOCC’s website and the COA website respectively. The statistical analysis shows that corporate governance does not have a significant impact on the annual audit opinion of GOCCs. However, the diminishing number of unqualified opinions and the decreasing mean of the financial component scores suggest that GOCCs have been implementing inadequate control systems in their financial reporting, posing threats to stability. Future researchers are encouraged to examine more recent data, consider different methodologies, and explore additional factors and perspectives. Keywords: Government-owned or Controlled Corporations (GOCC), State-owned Entities (SOE), corporate governance, performance scorecard (PES), audit opinion, Governance Commission for GOCCs (GCG), Commission on Audit (COA)